2010
DOI: 10.1177/0075424210374955
|View full text |Cite
|
Sign up to set email alerts
|

Diachrony and AAE: St. Louis, Hip-Hop, and Sound Change outside of the Mainstream

Abstract: In this article, the authors provide a diachronic analysis of the urr variable as it appears in African American English (AAE) spoken in St. Louis. While many believe that this linguistic feature is a product of hip-hop, invented recently for creative purposes, the authors provide linguistic evidence that shows it to be a prevalent feature of dialects of AAE spoken in St. Louis, Missouri, and East St. Louis, Illinois, at an earlier time. The authors suggest that the increase in vowel centralization that evolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…20 All of the second generation West Indians have some competency (i.e., can consciously code switch) in the English-lexifier Caribbean Creole spoken by their parents, in addition to dialects of American English. Blake and Shousterman (2010b) found quantitative differences in postvocalic /r/ vocalization in the speech of African Americans and West Indian Americans such that West Indian Americans retained postvocalic /r/ slightly more than African Americans. The authors argue that higher rates of /r/ retention among second generation Caribbean Americans may be tied to notions of class and prestige, as they were in Labov's (1966) department store study in New York City, and may be further elevated by the prestigious status of /r/ in the Caribbean (Wells 1982).…”
Section: Empirical Case Study: African American Language In New York mentioning
confidence: 89%
See 3 more Smart Citations
“…20 All of the second generation West Indians have some competency (i.e., can consciously code switch) in the English-lexifier Caribbean Creole spoken by their parents, in addition to dialects of American English. Blake and Shousterman (2010b) found quantitative differences in postvocalic /r/ vocalization in the speech of African Americans and West Indian Americans such that West Indian Americans retained postvocalic /r/ slightly more than African Americans. The authors argue that higher rates of /r/ retention among second generation Caribbean Americans may be tied to notions of class and prestige, as they were in Labov's (1966) department store study in New York City, and may be further elevated by the prestigious status of /r/ in the Caribbean (Wells 1982).…”
Section: Empirical Case Study: African American Language In New York mentioning
confidence: 89%
“…Importantly, African Americans are also participating in regional sound changes that are specific to their communities and not shared by White speakers in the area (cf. Pollock and Berni ; Blake and Shousterman ).…”
Section: Social Variation In African American Englishmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of AAVE in New York City found that adolescent African American speakers had 98% to 100% vocalization, considerably exceeding the white pattern (Labov et al, 1968, I:99-106). Blake and Shousterman (2010) track the development of this sound change within African American English in St. Louis and East St. Louis and trace its origins to Memphis. The general pattern shows an influence of the surrounding r-pronouncing mainstream dialect on an originally r-less AAVE.…”
mentioning
confidence: 99%